Hard drugs use in a black island society. - Stone, Carl (1991)
Reports on a national survey on drug use carried out in Jamaica in 1990. The study was intended to generate reliable base line data on the magnitude of the drug use problem in Jamaica and to provide important indicators with which to guide the demand reduction programmes and policies.